Green Tobacco Sickness pada Petani Tembakau - Dini Yusmita; Putu Devie Sri Astari (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Indonesia is the 6th largest tobacco producer in the world with a total tobacco production of 136 thousand tons or 1.91% of the world tobacco production. However, there are some negative impacts of these tobacco plants, especially for tobacco farmers. If farmers are too often make direct physical contact with tobacco plants, farmer at risk contracting green tobacco sickness. This disease is caused by the absorption of nicotine by the skin. Green tobacco sickness (GTS) has typical symptoms such as nausea, dizziness, headaches, stomach cramps, difficulty breathing, blood pressure and heart rate fluctuations and increased saliva. The incidence rate of Green tobacco sickness (GTS) starts when tobacco farmers work in the morning after rain, so the green tobacco leaves become wet and moist. It can be increases the risk of moisture containing 9 mg of dissolved nicotine per 100 mL dew, or the equivalent of nicotine content in six cigarettes. Another factor that influences is that tobacco farmers who work within one year have a higher risk than farmers who have worked in five years so there is need for work experience. The prevention than can be done are using personal protective equipment such as gloves, masks, boots when harvesting.